Bleaching as a complement to fluoride-enhanced remineralization or resin infiltration in masking white spot lesions - Talita Portela PEREIRA; Karin LANDMAYER; Bruna de Oliveira IATAROLA; Mariele VERTUAN; Ana Carolina MAGALHÃES; Luciana Fávaro FRANCISCONI- (University of São Paulo, 2024)
Abstract There are many suitable strategies for addressing caries, which is an ongoing worldwide problem. Although white spot lesions (WSLs) can be either remineralized naturally or treated with non- or micro-invasive strategies, their whitish and opaque appearance may persist. Objective To evaluate the effects of tooth bleaching as a complement to fluoride-enhanced remineralization or resin infiltration in masking WSLs, as well as in enamel surface roughness relative to that of the adjacent enamel. Methodology Flattened rectangular bovine enamel fragments (6×3×~2.9 mm length, width and thickness) were divided into six groups (L/N, F/N, F.BL/BL, I/N, I.BL/BL, N/N; n=15). Treatments applied to the 3×3 mm left half included: L (Lesion) - WSL simulation with 50 mM acetate buffer, 96 hours, 37ºC; F (Fluoride) - WSL treatment with 2% NaF neutral gel, 1x/week, 8 weeks; I (Infiltration) - WSL treatment with H3PO4 37%/10 s; Icon®-Dry/30 s; Icon®-Infiltrant/3 min+1 min; N (Nothing) - sound enamel/control. Treatments applied to both halves after F and I included: BL (Bleaching) - Opalescence Boost 40%, 3×/20 min each; N (Nothing) - control. The differences in color (ΔE00, ΔL, Δa, Δb) and surface roughness (ΔRa) between the left and right halves were measured. Kruskal-Wallis/post-hoc tests were applied to ΔE00, ΔL, Δa and ΔRa, and 1-way ANOVA/Tukey tests to Δb (α=0.05). Results The factor under study significantly influenced ΔE00 (p=0.0001), ΔL (p=0.0024), Δb (p=0.0015), and ΔRa (p<0.001), but not Δa (p=0.1592). Both fluoride-enhanced remineralization and resin infiltration were able to mask WSL, regardless of subsequent bleaching. However, when bleaching was performed, ΔE00 median values did not exceed the acceptability threshold for color difference. Only resin infiltration reduced ΔRa between WSL and the adjacent enamel. Conclusions Both remineralization and infiltration, particularly if complemented by bleaching, fostered satisfactory esthetic results. Only infiltration without bleaching led to really good results in surface roughness.